Employee Job Satisfaction in JHL Solitaire Gading Serpong - Rina Fitriana Fitriana; Deivy Zulyanti Nasution; Kemal Akbar (Fakultas Ekonomi, Universitas Bangka Belitung, 2020)
JHL Solitaire Gading Serpong is a hotel that carries an iconic, majestic and spectacular concept. This hotel is the first five-starred hotel in Banten by providing various luxurious facilities and equipment that makes it famous as “Jewel of The City”. This research aims to reveal the Influence of Human Resource Management on Employee Job Satisfaction in JHL Solitaire Gading Serpong. Data in this quantitative research gathered using questionnaire given to 100 employees of the hotel and then processed by SPSS 23. The result shows that the mean of human resource management in JHL Solitaire Gading Serpong is 4.65 stating the excellent human resource management already exists in JHL Solitaire, meanwhile the mean for the variable of employee job satisfaction in JHL Solitaire Gading Serpong is 4.65 stating very high of employee job satisfaction in JHL Solitaire. The influence of human resource management on employee job satisfaction in JHL Solitaire Gading Serpong is 98.21%, and the other 1.79% is influenced by other factors that are not involved in this study.